2001
DOI: 10.1037/0882-7974.16.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of resource allocation are reliable among younger and older readers.

Abstract: Younger and older adults read short expository passages across 2 times of measurement for subsequent comprehension or recall. Regression analysis was used to decompose word-by-word reading times into resources allocated to word- and textbase-level processes. Readers were more sensitive to these demands when reading for recall than when reading for comprehension. Patterns of resource allocation showed good test–retest reliabilities and were predictive of memory performance. Within age group, resource allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(121 citation statements)
references
References 68 publications
(139 reference statements)
5
112
4
Order By: Relevance
“…This has been demonstrated with respect to syntactic processing (Stine-Morrow, Ryan, & Leonard, 2000), textbase processing (Haberlandt et al, 1986;Miller & Stine-Morrow, 1998;Stine, 1990;Stine et al, 1995;Stine-Morrow, Milinder et al, 2001;Stine-Morrow, Miller et al, 2001;Titone et al, 2000), situation model construction (Morrow et al, 1997;StineMorrow et al, 2004), and narrative schema development (Stine-Morrow, Miller et al, 2001). …”
Section: Resource Allocation: Self-regulation As a Factor In Age Diffmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been demonstrated with respect to syntactic processing (Stine-Morrow, Ryan, & Leonard, 2000), textbase processing (Haberlandt et al, 1986;Miller & Stine-Morrow, 1998;Stine, 1990;Stine et al, 1995;Stine-Morrow, Milinder et al, 2001;Stine-Morrow, Miller et al, 2001;Titone et al, 2000), situation model construction (Morrow et al, 1997;StineMorrow et al, 2004), and narrative schema development (Stine-Morrow, Miller et al, 2001). …”
Section: Resource Allocation: Self-regulation As a Factor In Age Diffmentioning
confidence: 99%
“…Readers who demonstrate effective text memory allocate more time to (a) the elaboration of low frequency words, (b) the immediate processing of new concepts when they are introduced, and to (c) conceptual integration at the ends of constituents (Miller & Stine-Morrow, 1998;Stine-Morrow, Milinder et al, 2001;Stine-Morrow, Miller et al, 2001). Presumably, such variations in reading time reflect processing involved in the construction of an integrated textbase with distinctively encoded concepts, a process that supports subsequent search and retrieval.…”
Section: Resource Allocation: Self-regulation As a Factor In Age Diffmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in different studies, there have been no age differences in wrap-up times at clausal boundaries coupled with greater sentence boundary wrap-up effects for older adults (Smiler, Gagne, & Stine-Morrow, 2003) and larger wrap-up effects for older adults at both intrasentence and between sentence boundaries (Miller, Stine-Morrow, Kirkorian, & Conroy, 2004;). Interestingly, and consistent with the separate sentence interpretation resource hypothesis, resource allocation parameters for wrap-up apparently do not correlate with working memory as assessed by span measures (Smiler et al, 2003;Stine-Morrow, Milinder et al, 2001). Kemper et al (2001a) analyzed both cross-sectional and longitudinal language samples and found that syntactic complexity (e.g., the number of propositions or clauses in a sentence, types of syntactic structure used) declines gradually across the life span.…”
Section: A Sentence Comprehensionmentioning
confidence: 64%
“…Mixed findings for age effects in discourse comprehension and memory have been reported. Some studies have reported age deficits (e.g., Dixon, Hultsch, Simon, & von Eye, 1984;Hartley, Stojack, Mushaney, Annon, & Lee, 1994;Spilich, 1983;Zelinski & Burnight, 1997), whereas others have not (e.g., Mandel & Johnson, 1984;Meyer & Poon, 2001;Meyer & Rice, 1981;Stine-Morrow, Milinder, Pullara, & Herman, 2001;Tun, 1989). Some of the disparity in findings is due to the complexity of the interaction among text, task, reader, and strategy variables involved in reading (Meyer & Rice, 1983.…”
Section: Discussionmentioning
confidence: 99%